2004
DOI: 10.1038/sj.jhh.1001653
|View full text |Cite
|
Sign up to set email alerts
|

Early carotid atherosclerosis and cardiac diastolic abnormalities in hypertensive subjects

Abstract: Despite the fact that it is known that hypertension may be associated to early atherosclerosis manifestations, few data are to date available on the relationship between early carotid abnormalities and left ventricular diastolic dysfunction. To address this issue, 142 hypertensive patients (64 females and 78 males) younger than 55 years, at the first diagnosis of mild-tomoderate essential hypertension (WHO/ISH criteria), were selected from a database consisting of 3541 subjects referred to ultrasound cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…CIMT testing is a noninvasive imaging modality that has been shown to correlate to systemic atherosclerosis, structural heart disease, and atrial fibrillation and predicts the risk of recurrent stroke. [1][2][3][4][5][6][7] The correlation between and CIMT and CSE on TEE among patients with ischemic stroke has not been reported. Furthermore, the ability of a noninvasive testing strategy incorporating TTE bubble study for detection of intra-atrial communications and CIMT for detection of other CSEs has not been investigated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CIMT testing is a noninvasive imaging modality that has been shown to correlate to systemic atherosclerosis, structural heart disease, and atrial fibrillation and predicts the risk of recurrent stroke. [1][2][3][4][5][6][7] The correlation between and CIMT and CSE on TEE among patients with ischemic stroke has not been reported. Furthermore, the ability of a noninvasive testing strategy incorporating TTE bubble study for detection of intra-atrial communications and CIMT for detection of other CSEs has not been investigated.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7] Among patients with ischemic stroke, a low CIMT has been reported to have a high negative predictive value for the detection of complex aortic plaques, which are among the most prevalent CSE identified on TEE. 8 -13 Other evidence suggests that modern transthoracic echocardiography with bubble study is highly sensitive for the detection of intra-atrial communications, another commonly identified potential CSE after stroke.…”
mentioning
confidence: 99%
“…We found no association between E/A ratios and IMT in our population. Previous Western studies in hypertensive patients and with small sample size have shown that carotid IMT was associated with markers of diastolic function [29][30][31][32][33] such as isovolumic relaxation time and DT. However, data on the relationship between E/A ratio and carotid IMT were scarce, with only one Japanese study reported an unadjusted insignificant association.…”
Section: Arterial Stiffness and Left-ventricular Diastolic Dysfunctiomentioning
confidence: 99%
“…In certain populations, however, the prevalence becomes much higher: 15-25% in subjects with hypertension or PAD [8,9], and up to 70% in patients with CAD [10]. Our data showed a fairly high prevalence of subclinical carotid atherosclerosis in non-diabetic CKD patients; about half of the patients (54.4%) had carotid atherosclerosis, and most of them had carotid plaque.…”
Section: Discussionmentioning
confidence: 61%